An Analysis of the Reading Comprehension Difficulties Faced by Young Learners - Sofeny, Daniar; Arong, Asuda; Huda, Khoirul (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2022)
The purposes of this study were to know the student’s difficulties in reading comprehension, to know how the difficulties in reading occur, and to know why the difficulties in reading comprehension occur. The research used a qualitative descriptive method to describe the detail of students' difficulties in reading comprehension. To find out the result of the analysis that had been conducted and to describe the student's difficulties, the instrument the researcher used in this research are observation, interview, and documentation. The data sources were obtained from the second graders of Attawfikiyah Islamiyah School. The result showed that the students have difficulties finding the meaning of the words because their mastery of vocabulary is lacking. The students are difficulty also to get the main idea of the text. Thus, the students become do not like reading English texts and also difficult to answer the question of the reading text exercise. The next result from observation showed that there was a lack of facilities in supporting the teaching and learning process, especially for reading material. It can be concluded that the student’s difficulties in reading comprehension can occur when they lack English vocabulary, do not know the effective techniques in reading text, and lack facilities for the teaching and learning process.